DEVELOPMENT OF GOOGLE SITES-BASED LEARNING MEDIA INTEGRATED WITH PROJECT-BASED LEARNING FOR CATHOLIC RELIGIOUS EDUCATION - Lenni Sitanggang; Harun Sitompul; Abdul Hasan Saragih; R. Mursid (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to develop learning media using Google Sites in the Project-Based Learning (PjBL) model to improve the learning outcomes of Catholic Religious Education students in grade VIII of Santa Maria Middle School, Medan. This research is motivated by the low learning outcomes of students, the limited use of digital media in learning, and the less than optimal use of learning models that are able to accommodate the characteristics of the digital generation. The developed media is designed to integrate learning materials, project activities, interactive multimedia, digital portfolios, and learning reflections in one platform that is easily accessible to teachers and students. The research method used is Research and Development (R&D) with the ADDIE model, which includes stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of material experts, media experts, learning design experts, Catholic Religious Education teachers, and grade VIII students of Santa Maria Middle School, Medan. Research data were collected through questionnaires, observations, interviews, documentation, and learning outcome tests. Data analysis was carried out descriptively and quantitatively to assess the feasibility, practicality, and effectiveness of the developed product. The research results are expected to produce valid, practical, and effective Google Sites-based learning media to improve students' cognitive and affective learning outcomes. This media development is expected to support more interactive, collaborative, and contextual Catholic religious education learning and meet the demands of 21st-century learning.